2012
DOI: 10.1177/2047487312441724
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and risk factor control in patients after hospitalization for coronary heart disease: the EUROASPIRE III Study

Abstract: High prevalence of depression and anxiety in CHD patients, and relation with less frequent lifestyle modification, call to integrate methods of identification and minimizing unfavourable effects of depression and anxiety into the cardiac rehabilitation and prevention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
5
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 41 publications
4
64
5
10
Order By: Relevance
“…33 The risk of cardiac mortality among patients with CAD is increased by two to four times for those who have depression. 34 There was a high prevalence of comorbidity with both anxiety and depression, which has also been reported in other studies 8,9,[35][36][37][38] for depressive symptoms. Statistical data suggest that depression and anxiety frequently occur together.…”
Section: Discussionsupporting
confidence: 76%
“…33 The risk of cardiac mortality among patients with CAD is increased by two to four times for those who have depression. 34 There was a high prevalence of comorbidity with both anxiety and depression, which has also been reported in other studies 8,9,[35][36][37][38] for depressive symptoms. Statistical data suggest that depression and anxiety frequently occur together.…”
Section: Discussionsupporting
confidence: 76%
“…This fact confirms our results since they indicated percentages of anxiety and depression in women in our sample (66.1% and 46.4% respectively) higher than those of men (50% and 26.9% respectively). It is worth reflecting on these results, since the evidence suggests that the treatment of negative psychosocial factors, such as anxiety and depression, help individuals with CVD to recover, reducing the number of events and improving their quality of life (Olafiranye et al, 2011;PerK et al, 2012;Pajak et al, 2013;McSweeney et al, 2016). With regard to marital status, the multivariate analysis in our study revealed that it is not statistically significant; however, women are less likely to be married.…”
Section: Discussionmentioning
confidence: 53%
“…It is worth noting that as well as negative emotional states being common in individuals with CVD, they negatively affect their quality of life, adherence to recommended treatments, the costs of care as well as the recovery from the disease and are associated with a large comorbidity and mortality. Their presence also promotes the exacerbation of traditional risk factors and adopting less healthy behaviours (Olafiranye et al, 2011;PerK et al, 2012;Pajak et al, 2013). Among the most widely studied psychosocial risk factors is depression, whose evidence confirms it as a factor favouring increased cardiovascular risk.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…high among CHD patients in general, and indicated that no history of invasive treatment is associated with more frequent depression and anxiety in hospitalized CHD patients (35).…”
Section: Discussionmentioning
confidence: 99%